The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s0006-87052008000400029
|View full text |Cite
|
Sign up to set email alerts
|

Tamanho mínimo de parcela para avaliação de caracteres de raiz em cenoura

Abstract: A estimação do número ideal de plantas para a avaliação de populações de cenoura é importante para que se possa reduzir o erro experimental e, com isso, maximizar a precisão das informações obtidas em um experimento, além de contribuir sobremaneira para a redução de recursos financeiros empregados na pesquisa. O objetivo do trabalho foi estimar o número mínimo de plantas por parcela para avaliação de caracteres de raiz em ensaios de populações de cenoura utilizando os métodos de máxima curvatura modificado e d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
(6 reference statements)
1
5
0
1
Order By: Relevance
“…These results are similar to those found by Vieira and Silva (2008) and Henriques Neto et al (2009), who indicated that for each situation, crop management, there must be a proper PS, which should not be generalized. This was the case with the various estimation methods.…”
Section: Applicationssupporting
confidence: 91%
“…These results are similar to those found by Vieira and Silva (2008) and Henriques Neto et al (2009), who indicated that for each situation, crop management, there must be a proper PS, which should not be generalized. This was the case with the various estimation methods.…”
Section: Applicationssupporting
confidence: 91%
“…According to Oliveira et al (2006) and Vieira & Silva (2008), in order to determine the ideal size of plots, it is important to use more than one methodology, due to the variation that may exist in the estimates of each one. For the coefficient of repeatability, we found that the number of measurements in the plots necessary to predict the true value of the genotypes with coefficient of determination (R2) of 90%, in the mean of the replicates and the methodologies used, it ranged from 9.74 to 13.34, and with R2 of 95% it ranged from 20.56 to 28.15 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…For the determination of the minimum number of plants, by the modified maximum curvature method, the expression presented by Chaves (1985) apud Vieira & Silva (2008) was used: N = [a2 b2 (2b-1) / (b-2)]1 / (2 -2 b), where "a" is the regression constant and "b" is the regression coefficient estimated from the adjustment of the model presented by Chaves (1985) apud Vieira & Silva (2008), considering the coefficient of variation and the number of plants per plot.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of replications and/or, the ideal plot size to estimate genetic parameters or compare progenies and/or cultivars, were also investigated and satisfactorily determined, varying with the crop and trait considered (Storck et al 2007, Vieira and Silva 2008, Leite et al 2009, Cargnelutti Filho et al 2010, Silva et al 2011, Storck et al 2011and Cargnelutti Filho et al 2012). …”
Section: Introductionmentioning
confidence: 99%